Syntactic agreement in authentic audio-visual input: Implications for ELT grammar instruction from an Indonesian EFL film - Dinar Dipta; Zeny Luthvia; Eta Lica Hanan Nadifa; Norhayati binti Haji Abd Karim (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
Syntactical agreement is a pivotal grammatical relation that ensures coherence between elements in a clause, particularly in terms of number, gender, and person. Failing to master it results in grammatical errors that undermine communication. Focusing on the Inthiq! 2-Speak English! film by Gontor TV, the research aims to identify the types of agreement employed by the characters and their appropriateness across different agreement structures. Employing a qualitative content analysis design, data were collected from the film’s transcription and analyzed using established grammatical frameworks and relevant previous studies. The findings reveal two major agreement types: subject-verb agreement (55 occurrences) and pronoun-antecedent agreement (10 occurrences). Through a systematic analysis of these patterns, the researcher examines how accurately and consistently agreement forms are used in authentic dialogue and interprets how these naturally occurring examples can be transformed into pedagogical materials. The study highlights its relevance to EFL instruction by demonstrating that authentic media, particularly locally produced films, can serve as effective resources for teaching grammatical agreement, enhancing learners’ syntactic awareness, and illustrating real-life language use. The findings suggest that agreement patterns are predominantly simple and consistent, reflecting simplified spoken input rather than full natural complexity. Overall, the results provide both linguistic insights and practical implications for integrating audio-visual materials into EFL teaching.